2017
DOI: 10.1016/j.jpha.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical determination of an anti-hyperlipidimic drug pitavastatin at electrochemical sensor based on electrochemically pre-treated polymer film modified GCE

Abstract: An electrochemically pretreated silver macroporous (Ag MP) multiwalled carbon nanotube modified glassy carbon electrode (PAN-Ag MP-MWCNT-GCE) was fabricated for the selective determination of an anti-hyperlipidimic drug, pitavastatin (PST). The fabricated electrochemical sensor was characterized by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The fabricated electrode was employed in quantifying and determining PST through differential pulse adsorptive stripping voltammetry (DPAdSV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…As some other authors have reported, a variety of excipients including cellulose, starch, talc, titanium dioxide, sodium lauryl sulfate, lactose, among others, do not interfere with the electrochemical signal of different APIs using different carbon-based working electrodes, even at excipient concentrations ranging from 60 to 100 times higher than the API. [45][46][47][48][49] Likewise, for the electrochemical study of PAR from different authors, no excipient interference was observed. [50][51][52] Since the modified electrodes will be in a solution at 37…”
Section: Interferents Study Electrode Stress Test and Surface Saturationmentioning
confidence: 87%
“…As some other authors have reported, a variety of excipients including cellulose, starch, talc, titanium dioxide, sodium lauryl sulfate, lactose, among others, do not interfere with the electrochemical signal of different APIs using different carbon-based working electrodes, even at excipient concentrations ranging from 60 to 100 times higher than the API. [45][46][47][48][49] Likewise, for the electrochemical study of PAR from different authors, no excipient interference was observed. [50][51][52] Since the modified electrodes will be in a solution at 37…”
Section: Interferents Study Electrode Stress Test and Surface Saturationmentioning
confidence: 87%
“…Approximately 200 cells were used from each developmental stage to investigate the TET protein level by electrochemical techniques. Sample preparation, electrochemical measurement, and data analysis were performed as described in previous studies ( Ozcan et al, 2017 ; Pandit et al, 2017 ; Wang et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies reported that the TET protein family, which includes important enzymes of DNA demethylation, is regulated by O-glycosylation, and plays an important role in maintaining the stemness of stem cells (Zhang et al, 2014;Hahn et al, 2019;Ross and Bogdanovic, 2019;Yu et al, 2019). The dynamic protein levels of TET were investigated by electrochemical techniques because of their high sensitivity, low instrumentation cost, relatively shorter analysis times, and lack of tedious extraction procedures when compared with other analytical techniques (Pandit et al, 2017). The size and shape of the prepared PANI and AuNPs were examined by a scanning electron microscope.…”
Section: Dynamic Tet Analyzed In Mammalian Oogenesis and Preimplantatmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the pH value of detection solution has a great influence on both electrochemical performance of sensor and activity of biomolecules. 29,31,32 Moreover, electrochemical redox reaction is significantly influenced by proton concentration, thus variation of sample pH results in analytical response variations. In particular, the acidic solution can affect to reduction behavior of SNP as described above.…”
Section: Detection Sensitivitymentioning
confidence: 99%